THE ROLE OF PRIVATE CLINICS IN PUBLIC HEALTH CARE - Pulatova Lola Uktamjonovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In the course of reforms carried out in the years of independence in the field of health care, special attention was paid to the development of private sector activities along with state medical institutions. Strengthening all-round support for the development of the private sector in the health sector, creating the necessary conditions for private medical institutions to provide high-tech quality medical services to the population, expanding foreign investments, and attracting highly qualified specialists to the private medical sector, as well as medical tourism and to develop the export of medical services.